A fieldable electrostatic air sampler enabling tuberculosis detection in bioaerosols. (January 2020) - Rufino de Sousa, Nuno; Sandström, Niklas; Shen, Lei; Håkansson, Kathleen; Vezozzo, Rafaella; Udekwu, Klas I.; Croda, Julio; Rothfuchs, Antonio Gigliotti
Abstract: Tuberculosis (TB) infects about 25% of the world population and claims more human lives than any other infectious disease. TB is spread by inhalation of aerosols containing viable Mycobacterium tuberculosis expectorated or exhaled by patients with active pulmonary disease. Air-sampling technology could play an important role in TB control by enabling the detection of airborne M. tuberculosis, but tools that are easy to use and scalable in TB hotspots are lacking. We developed an electrostatic air sampler termed the T B H otspot DetectOR (THOR) and investigated its performance in laboratory aerosol experiments and in a prison hotspot of TB transmission. We show that THOR collects aerosols carrying microspheres, Bacillus globigii spores and M. bovis BCG, concentrating these microparticles onto a collector piece designed for subsequent detection analysis. The unit was also successfully operated in the complex setting of a prison hotspot, enabling detection of a molecular signature for M. tuberculosis in the cough of inmates. Future deployment of this device may lead to a measurable impact on TB case-finding by screening individuals through the aerosols they generate.